Refleksi Normatif Mengenal Sahifah al-Madinah Terhadap Konstitusi Negara Indonesia - Hanif Fudin Al-Azhar (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2018)
In the life of the nation, each country has specific guidelines to regulate and bind the people in the country, including governance arrangements. This paper is intended to discuss and examine those specific guidelines as the state constitution. The focus of this study is the constitution of the Republic of Indonesia, namely the post-Amendment 1945 Constitution which is considered implicitly relevant to á¹¢aá¸¥Ä«fah al-MadÄ«nah or Medina Charter as the result of the agreement between Rasulullah SAW and people of Madinah at that time (Mu'aqadah al-Waá¹Äniyah). It is considered to have constitutional content as in constitution of a modern state. The author uses the reflective aspect of á¹¢aá¸¥Ä«fah al-MadÄ«nah normatively in terms of constitutional content in the Republic of Indonesia